Modeling a non-Newtonian nanofluid flow between intersecting planes with slip mechanism - Rehman, Sohail; Hashim; Alqahtani, Sultan; Alshehery, Sultan (Continuum mechanics and thermodynamics, 2023)
The present article is framed to address the Jeffery–Hamel flow of a generalized Newtonian fluid between two intersecting plane walls subject to viscous dissipation and slip mechanisms. The transport equations for nanofluids are formulated using the Buongiorno model along with the Carreau constitutive model. The strongly nonlinear system of partial differential equations involving momentum, energy and concentration conservations is modelled for purely radial flow. The reduced system of ordinary differential equations is numerically handled via shooting approach with implicit Runge–Kutta–Butcher and Nachtsheim–Swigert iteration techniques. The precise details of the numerical outcomes of the current investigation are presented via velocity, temperature, concentration, friction coefficient, Nusselt and Sherwood numbers for various involved parameters within converging/diverging zone with semi-apex angle of the channel. The results of this study tend to show that velocity slip factor reduces the fluid velocity in converging channel more dominantly in contrast to the diverging channel. On the other hand, temperature and concentration are dwindle with the manifestation of temperature and concentration slips. The Carreau fluid parameter such as Weissenberg and power index exhibits opposite behavior for velocity and temperature fields. In a limiting context, the present results are compared with those of an already published study. A strong alignment between the numerical values is noted. The results of present study have possible applications in flow through nozzles, diffusers, and reducers in polymer processing.